CULTURE AND RELIGION VALUE IN E-ENGLISH TEXTBOOK FOR JUNIOR HIGH SCHOOL: A CONTENT ANALYSIS - Nurul Lailatul Khusniyah; Indah Khomsiyah (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2019)
The aim of this study is to know the culture and religion value contains in an English textbook for junior high school. Culture and religion have integrated into each utterance that is in the textbook. The study used the qualitative approach through a content analysis method. The procedure value analysis used Byram’s theory. Data were taken from an utterance in each chapter. The result of the data analysis found that belief and behaviour have 22,8%, socialization and life cycle has 60%, stereotypes and national identity has 11,4%, and Social and political institution has 5,8%. The value that dominates in the textbook is socialization and life cycle. The material in the textbook concern to a local and simple concept.